INOVASI LITERASI MELALUI BARESTA di ERA 4.0 (Studi Kasus di MTs Negeri 3 Jombang) - Nurul Swandari; Jemani, Abdurahman (Lembaga Bale Literasi, 2023)
Growing and honing active and receptive language skills can be done by cultivating a passion for reading. By liking reading, it will train students to understand and interpret information and encourage them to develop critical thinking skills. This manuscript is a case study that involves the author carrying out and observing thoroughly and continuously an activity carried out by students. The aim of this Best Practice is to build the character and love of reading for MTsN 3 Jombang students through the Baresta strategy. The method used in implementing this Best Practice is experiential learning (experience-based), namely providing opportunities for students (grades VII, VIII, and IX) to apply their reading experience in writing and speaking activities, which is carried out over three semesters, namely the odd semester and the second semester. even 2021/2022 and odd 2022/2023. The results achieved in this activity are the honing of receptive and active language skills (reading, writing resumes, telling the contents of a book) and being able to publish either verbally or using YouTube, and practice critical thinking in answering questions.